Análise do acervo de Leguminosae Juss. do herbário da Universidade Federal do Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
The data on Leguminosae Juss. registered in the virtual herbarium associated with the Herbarium of the Federal University of Western Pará (HSTM) was analyzed. Accessing the database through the Jabot Management System and extracting information from each specimen. The analysis showed a total of 2,089 specimens. Of these, 64% (1,337) were identified to species level, approximately 31% (641) to genus level and around 5% (111) to family level. The taxonomic diversity of Leguminosae recorded in the HSTM collection is 127 genera and 388 species. The three most diverse genera are Inga Mill., Chamaecrista (L.) Moench and Swartzia Schreb., in line with the flora of Brazil for the number of species cataloged for the Amazon. The records show that the Leguminosae in the HSTM collection are present in all environments in the region, mainly in forests, and that tree species predominate. Nineteen records with nomenclatural spelling errors and three records with family errors were detected and corrected. Synonyms and updates to genus and species names in line with the Flora e Funga do Brasil and Legume Data Portal databases totaled 47 records. The distribution of Leguminosae collection points showed that there are three areas with no botanical collection coverage in the municipalities surrounding Santarém: Aveiro, Juruti, Mojuí dos Campos and Prainha. A recommendation is made to improve the analysis of data from botanical collection records: protocols for collecting information from field data.
Keywords: Fabaceae; Análise de dados; Coleções biológicas; Herbário; CNPQ:: CIÊNCIAS BIOLÓGICAS